Competency-based English language teaching through Microsoft teams: A framework for adaptation and integration - Prasetya, Rizky Eka (Universitas Muhammadiyah Malang, 2024)
This paper addresses the challenge of implementing Competency-Based English Language Teaching (CBELT) within the digital realm, specifically through the utilization of the Microsoft Teams platform. The methodology employed Mix-method with incorporating exploratory sequential design. Qualitative data from the interviews will be analyzed using thematic analysis to identify recurring patterns, themes, and key considerations for implementing CBELT in Microsoft Teams. Surveys assessed pedagogical and technical efficacy in descriptive statistics and correlation analysis in the quantitative phase. The finding of the research exposed that Educators emphasized leveraging Microsoft Teams' features like chat, video conferencing, and file sharing to deliver CBE content effectively. With a mean score of 4.49, most respondents were satisfied with CBE integration with Microsoft Teams. This suggests the platform's CBE integration is well-received. Respondents reported a mean score of 6.23 for language proficiency development with Microsoft Teams CBE. Microsoft Teams is simple to use, according to respondents, with a mean score of 6.62. A moderate positive association exists between project-based learning intensity and competence development results (r = 0.664, p < 0.05). This shows that increasing project-based learning intensity improves student proficiency. A moderate positive association exists between integrating collaborative activities and engagement indicators (r = 0.657, p < 0.05). This suggests that Microsoft Teams collaborative activities boost student engagement during Competency-Based English Language Teaching (CBELT). Project-based learning, collaborative activities, and customised teaching help CBE succeed. These tactics allow students to actively learn, contribute, and get individualised teaching.